Leveraging Business Analytics for Enhanced Decision-Making Navigating Challenges and Exploiting Opportunities - Mazher, Muhammad Ahmad; Tramankuti, Yasotha Nair (Future Science / FSH-PH Publications, 2024)
Business analytics (BA) is revolutionizing how businesses use data to gain a competitive advantage. It offers opportunities for deeper customer insights, targeted marketing campaigns, improved customer satisfaction, new product and service opportunities, and optimized business processes. However, challenges like data quality, talent acquisition, and ethical considerations exist. This study reviews BA literature and discusses the challenges faced by organizations in implementing business analytics, including data availability, quality, skills and training, and technology infrastructure considerations. We conducted a study on 133 analytics professionals in Lahore, Pakistan. Data availability and quality, skills and training, and technology infrastructure all had a positive and significant impact on business analytics challenges and opportunities. The findings aim to contribute to a better understanding of business analytics, implementation challenges, and opportunities.